STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA DALAM LEMBAGA PENDIDIKAN ISLAM ERA SOCIETY 5.0 - Farah Hasanah Noor; Zainal Berlian; Baharudin (STKIP Subang, 2026)
The Society 5.0 era demands the transformation of human resource development (HRD) in Islamic educational institutions to balance digital competencies with Islamic values. This article aims to analyze strategies for developing human resources for teachers and educational staff in the context of Islamic education management in the Society 5.0 era. This study employs a qualitative approach using a literature review method. The findings indicate that the most relevant strategies include digital competency training, mentorship programs, spiritual guidance, technology-based performance evaluation, and innovation in the Islamic Religious Education (PAI) curriculum based on AI and big data. These strategies are expected to enhance the quality of human resources in Islamic education institutions, making them adaptive to technological disruption while maintaining their Islamic identity.